Role of neuro-sonography of peripheral nerves as a diagnostic and a differentiation tool of amyotrophic lateral sclerosis - Rana Zakaria Ahmed Mohamed; Haitham Hamdy Salem; Hossam Moussa El-Sayed Sakr; Hossam-Eldin Mahmoud Afifi; Ahmed Mohammed Elsadek; Nagia Aly Fahmy (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2021)
Abstract Background Motor neuron disease is a heterogeneous group of progressive neurodegenerative disorders, most common of which is amyotrophic lateral sclerosis (ALS). There are many clinical and radiological criteria to diagnose amyotrophic lateral sclerosis and to differentiate it from other motor neuron disease and neurodegenerative disorders. Neuro-sonography is one of the easily applied tools to diagnose and differentiate ALS. ALS diagnosis is delayed up to 3 years according to some authors due to the wide differential diagnosis, with cervical degeneration being a common misdiagnosis. The objective of this study was to evaluate the role of neuro-sonography in diagnosis and differentiation of amyotrophic lateral sclerosis from other causes of progressive mixed upper and lower motor neuron lesion. Results A total neuro-sonography score at a cut-off point (≤ 127) predicted patients with ALS, with good (85%) accuracy, sensitivity = 73% and specificity = 83% (p < 0.01) and Lt median arm score at a cut-off point (≤ 6) predicted patients with ALS, with good (88%) accuracy, sensitivity = 86% and specificity = 86% (p < 0.01) and the median nerve at the arm level was the most sensitive and specific nerve to predict patients with ALS. Conclusion Neuro-sonography of peripheral nerves is a recent, noninvasive, accessible technique that can be used in early diagnosis of ALS.